ميراث المرأة في بلاد يوربا النيجيرية بين الشريعة والقانون : دراسة تحليلية - Shittu Bilal Yusuf
Before the advent of Islam, a woman was an object of humiliation and contempt. However, Islam came to suppress the degradation and humiliation, among other things. In Yoruba-land, there is an oppression of the woman by depriving her certain share from the estate left by the late husband. The researcher studied the woman’s inheritance in Yorubaland by making an analytical and comparative study between the Yoruba traditional law and Sharĩʻah. He then explained the issue of woman’s inheritance in the society, whereby she is deprived of having a share from the estates left by her husband; or she is maltreated and considered as part of the estates. The researcher elucidated the people’s little knowledge of Islamic law of inheritance, because it is one of the main causes of the continuity of the problem. He highlighted the ambiguities associated with the share of the woman in inheritance which is half of the man’s share- as it is believed by some people to be an injustice to her. He revealed the role played by the scholars, court, societies and human right organizations towards solving this problem in Yorubaland and explained some ways of improving the staus quo of inheritance in the society. The researcher adopted the inductive and descriptive analytical methods, coupled with the field study that involves interviews with some concerned personalities. This was done in order to sample their opinions which might enhance positive results. At last, the researcher came out with a number of factors hindering the effectiveness of all efforts made towards solving the problem of denying a woman her right to inheritance. The notables of the factors include people’s lack of religious knowledge, lack of united efforts by the scholars addressing the issue, no government’s support, and weakness in applying the provision emphasizing freedom of religion in Nigerian constitution. After all it is possible to check the factors by creating awareness among the people, and educating them on their religious affairs; while Arabic-Islamic schools should be teaching the subject of Inheritance. Also, there must be united efforts by the scholars, Islamic leaders, the preachers and organizations on the application of Islamic law, and a number of Sharĩʻah courts should be established in Yoruba-land, like the situation in the Northern part of the country since time immemorial- whereby the Islamic law will be applied to many transactions including the inheritance.